Intestinal subocclusion and severe malnutrition in systemic sclerosis without scleroderma - Valenzuela-Rodríguez, Germán (2023)
Systemic sclerosis sine Scleroderma is an uncommon form of systemic compromise of this disease, in the abscense of cutaneous manifestations. We present the case of a 71 years-old woman, body mass index (BMI) in 16.9 kg/m2, with history of hypothyroidism and chronic constipation, who goes to the emergency with pain, abdominal bloating, and nausea. An abdominopelvic tomography was made, reporting a collapse of the gastric chamber, some segments of intestinal loops distended with signs of fecalization in the small intestine. A colonoscopy described severe dolicocolon. We observed indurated plaques in left elbow and in both buttocks. Lab tests: ANA 1/640 with anticentromeric pattern, anticentromere antibodies = 227 U/mL (0-25), Anti-SCL-70 = 1.9 U/mL (0-25), anti-RNP = 0.1 U/mL (0-25). Peri-ungueal cappilaroscopy 200x showed mega capillaries. Clinical diagnosis was systemic sclerosis sine scleroderma. We initiated treatment with a high-fiber diet and parenteral nutrition for a week. The patient evolution was favorable.